COMMUNITY EMPOWERMENT IN REDUCING UNEMPLOYMENT THROUGH AL-RUFA'I TEMPE MAKING BUSINESS IN KEDUNGJAYA VILLAGE, SUB-DISTRICT KEDAWUNG DISTRICT, CIREBON - Fata, M. Anissul; Amalia, Amah; Trimayanti, Imas; Fitralisma, Gian; Yanthi, Winda Dwi; Solihah, Nur Apriani; Nur Fitriani , Ade Febry; Fawaiz, Rohmatul (Ann Publisher, 2025)
Abstract: Background. According to Luluatul Fu'adah, Agus Suherman & Fitria Firdiyani (2024) Community empowerment is a strategic effort to develop community independence and welfare through increasing knowledge, skills, behavior and abilities. Aims. The aim of this research is to determine community empowerment activities through the tempe business in Kedungjaya Village, Kedawung District, Cirebon Regency. It is hoped that this research can provide useful information for the government and society in developing more effective and sustainable community empowerment programs. This is very important in facing the economic and social challenges faced by society, especially in Cirebon Regency. Methods. According to data published by the Cirebon Regency Central Statistics Agency (BPS), the poverty line in 2024 shows a fairly high figure, namely IDR 475,046 per capita per month. This means that people living below the poverty line have to struggle to meet their basic needs. Compared to 2023, this poverty line has increased by 5.13 percent, from IDR 451,853 per capita per month. Good news in efforts to reduce the severity of poverty in Cirebon Regency. The poverty severity index (P2) shows a significant decline, from 0.53 in 2023 to 0.36 in 2024. Conclusion. This shows that the government and society's efforts to reduce poverty are starting to bear fruit. Even though there are still many challenges that must be faced, the reduction in the poverty severity index gives hope to the people of Cirebon Regency. By continuing to increase innovative efforts and strategies that create small economic jobs and increase people's income. Implication. Like the tempeh business in Kedungjajang Village, Cirevon Regency. Therefore, community empowerment is a force to increase the income and economy of the small community of Kedungjaya Village.